In vitro and in vivo single-agent efficacy of checkpoint kinase inhibition in acute lymphoblastic leukemia. Issue 1 (December 2015) - Iacobucci, Ilaria; Di Rorà, Andrea; Falzacappa, Maria; Agostinelli, Claudio; Derenzini, Enrico; Ferrari, Anna; Papayannidis, Cristina; Lonetti, Annalisa; Righi, Simona; Imbrogno, Enrica; Pomella, Silvia; Venturi, Claudia; et al.
Abstract Background Although progress in children, in adults, ALL still carries a dismal outcome. Here, we explored the in vitro and in vivo activity of PF-00477736 (Pfizer), a potent, selective ATP-competitive small-molecule inhibitor of checkpoint kinase 1 (Chk1) and with lower efficacy of checkpoint kinase 2 (Chk2). Methods The effectiveness of PF-00477736 as single agent in B-/T-ALL was evaluated in vitro and in vivo studies as a single agent. The efficacy of the compound in terms of cytotoxicity, induction of apoptosis, and changes in gene and protein expression was assessed using different B-/T-ALL cell lines. Finally, the action of PF-00477736 was assessed in vivo using leukemic mouse generated by a single administration of the tumorigenic agentn -ethyl-n -nitrosourea. Results Chk1 and Chk2 are overexpressed concomitant with the presence of genetic damage as suggested by the nuclear labeling for γ-H2A.X (Ser139) in 68 % of ALL patients. In human B- and T-ALL cell lines, inhibition of Chk1/2 as a single treatment strategy efficiently triggered the Chk1-Cdc25-Cdc2 pathway resulting in a dose- and time-dependent cytotoxicity, induction of apoptosis, and increased DNA damage. Moreover, treatment with PF-00477736 showed efficacy ex vivo in primary leukemic blasts separated from 14 adult ALL patients and in vivo in mice transplanted with T-ALL, arguing in favor of its future clinical evaluation in leukemia. Conclusions In vitro, ex vivo, and in vivo results support the inhibition of Chk1 as a new therapeutic strategy in acute lymphoblastic leukemia, and they provide a strong rationale for its future clinical investigation.